Strategi Pemasaran dalam Meningkatkan Penjualan Ayam Geprek Aroma - Maina, Maina; Usman, Usman (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to find out the marketing mix strategy in the Ayam Geprek Aroma culinary business in conducting marketing that utilizes social media such as Facebook and Whatsapp which can affect consumers' buying interest in Ayam Geprek Aroma food. The marketing strategy used is products, prices, promotions, and places in marketing so that it can increase the sales turnover of Ayam Geprek Aroma. This study uses a type of qualitative research with a descriptive method. Data collection techniques are carried out by observation, direct interviews, and documentation. The results of this study also show that marketing strategies carried out through social media such as Facebook and Whatsapp as a marketing medium are quite effective, because many consumers use Facebook and Whatsapp more often to order Ayam Geprek Aroma products. As for the marketing mix of Ayam Geprek Aroma products, the quality has been guaranteed and product development can meet the wishes of consumers, as well as product prices that are affordable for all groups because they are relatively cheap. Promotions carried out through social media Facebook, Whatsapp and offline have a very good impact on Ayam Geprek Aroma products. The marketing mix strategy that most affects consumer buying interest is the price where Ayam Geprek Aroma is sold at a low price, but the taste is no less competitive with other products